120k views
0 votes
HELP PLEASE!!!! I NEED IT ASAP!

Consider the System of equations:

5x- 2y = 16
15x- 7y = 51
Multiply the first equation by some constant, so that in the resulting equation, the coefficient of x matches the coefficient of x in the second equation.
Enter the entire equation that results from multiplying the first equation by the constant.

User Rahimli
by
5.0k points

1 Answer

3 votes

Answer:

y = -3 and x = 2

Explanation:

Multiply 1st equation by - 3 and add with second equation you will get -y = 3 and you will substitute y to the 1st equation

User MPikkle
by
5.5k points